THE MEDIATING ROLE OF INCOME LEVEL IN THE RELATIONSHIP BETWEEN FINANCIAL LITERACY, FINANCIAL GOALS, AND RETIREMENT PLANNING - Hadi Ismanto; Mirawati Mirawati (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to gather concrete evidence on how financial literacy and financial goals influence retirement planning, with income level as a mediator. This research is driven by the public's need to manage their finances wisely and plan for retirement, especially as the economy becomes increasingly unstable and many people in Indonesia are not actively involved in retirement programs. Unlike previous research that typically focuses only on the direct relationship between variables, this study adds new insights by including income level as a mediator, demonstrating how financial literacy and financial goals can influence retirement planning, especially in developing countries. Data were collected using questionnaires administered to 106 working-age individuals in Indonesia. This study used the Structural Equation Modeling (SEM-PLS) method to test the direct and indirect relationships between the various variables. The findings indicate that having good financial knowledge and clear financial goals leads to better retirement planning, both directly and by influencing one's income. These results suggest that people who are more knowledgeable about money and have a clear financial plan are more likely to plan well for retirement, as greater financial knowledge and a clear direction can help them earn a higher income. This research adds to existing research on retirement planning by demonstrating how income level plays a key role in linking financial capability to long-term financial actions. This research suggests that governments and financial institutions should improve financial education programs to help people set and achieve financial goals, thereby strengthening financial skills and increasing readiness for retirement.